Exonerees in Black and White: the influence of race on perceptions of those who falsely confessed to a crime. Issue 9 (21st October 2019) - Howard, Simon
ABSTRACT: Black Americans account for 61% of those who have been released from prison through DNA exoneration. In the present study, we explored the influence of race on perceptions of wrongfully convicted individuals who have been exonerated. Participants ( N = 121) were randomly assigned to read a fictional newspaper article about a Black or White individual who was wrongfully convicted due to a false confession and then report their perceptions of the exoneree's guilt, warmth, competence and aggression, how deserving the exoneree was of government assistance and the likelihood that once released, the exoneree would commit a crime resulting in his reimprisonment. Results indicated that a Black exoneree was perceived as more aggressive (but not less competent or warm), less deserving of assistance, and more likely to commit a crime post exoneration resulting in his reimprisonment than a White exoneree. We also explored whether there were differences in terms of race on perceptions of mental illness for those wrongfully convicted due to falsely confessing to a crime and found that participants perceived a White exoneree as more mentally ill than a Black exoneree. The implications for the post-incarceration experiences and challenges faced by Black exonerees relative to White exonerees are discussed.